Circulating tissue inhibitor of metalloproteinases 1 (TIMP-1) at COVID-19 onset predicts severity status - Brusa, Stefano; Terracciano, Daniela; Bruzzese, Dario; Fiorenza, Mariano; Stanziola, Lucia; Pinchera, Biagio; Valente, Valeria; Gentile, Ivan; Cittadini, Antonio; Mormile, Ilaria; Mormile, Mauro; Portella, Giuseppe (Frontiers in Medicine, 2022)
Background: Systemic biomarkers for severity of SARS-CoV-2 infection are of great interest. In this study, we evaluated a set of collagen metabolites and extracellular matrix remodelling biomarkers including procollagen type III amino terminal propeptide (PIIINP), tissue inhibitor of metalloproteinases 1 (TIMP-1) and hyaluronic acid (HA) as prognostic indicators in COVID-19 patients. Methods: Ninety COVID-19 patients with the absence of chronic liver diseases were enrolled. Serum PIIINP, TIMP-1 and HA were measured and correlated with inflammatory indices and clinical variables. Patients were stratified for disease severity according to WHO criteria in two groups, based on the requirement of oxygen support. Results: Serum TIMP-1, but not PIIINP and HA was significantly higher in patients with WHO score > 5 compared to patients with WHO score < 5 [PIIINP: 7.2 (5.4–9.5) vs. 7.1 (4.5–9.9), p = 0.782; TIMP-1: 298.1 (20.5–460) vs. 222.2 (28.5–452.8), p =0.01; HA: 117.1 (55.4–193.7) vs. 75.1 (36.9–141.8), p =0.258]. TIMP-1 showed moderate correlation with CRP (r = .312, p =0.003) and with LDH (r=0.263, p=0.009). CRP and serum LDH levels were significantly higher in COVID-19 patients with WHO score > 5 compared to the group of patients with WHO score <5 [15.8 (9–44.5) vs. 9.3 (3.4–33.8), p= 0.039 and 373 (282–465) vs. 289 (218–383), p= 0.013, respectively]. Conclusion: In patients with COVID-19, circulating TIMP-1 was associated with disease severity and with systemic inflammatory index, suggesting that TIMP-1 could represent a promising non-invasive prognostic biomarker in COVID-19 patients. Interestingly, our results prompted that serum TIMP-1 level may potentially be used to select the patients for therapeutic approaches targeting matrix metalloproteases pathway.